2007
DOI: 10.1086/510560
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of Common Copy-Number Variations in the Human Genome

Abstract: Segmental copy-number variations (CNVs) in the human genome are associated with developmental disorders and susceptibility to diseases. More importantly, CNVs may represent a major genetic component of our phenotypic diversity. In this study, using a whole-genome array comparative genomic hybridization assay, we identified 3,654 autosomal segmental CNVs, 800 of which appeared at a frequency of at least 3%. Of these frequent CNVs, 77% are novel. In the 95 individuals analyzed, the two most diverse genomes diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
406
3
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 478 publications
(440 citation statements)
references
References 33 publications
22
406
3
9
Order By: Relevance
“…In an analogy to Wong et al, 32 we assumed that CNCs are identical to the BAC probe representing them. This has been confirmed by SNP array mapping of break points in a small sample from our patient cohort (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In an analogy to Wong et al, 32 we assumed that CNCs are identical to the BAC probe representing them. This has been confirmed by SNP array mapping of break points in a small sample from our patient cohort (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…After analysis, the averages of all triplicate spots were calculated. Subsequently, data were analyzed essentially according to Wong et al 32 Briefly, all spots with an aberrant shape, signal to noise ratios o5.0 or with an SD above 0.3 were excluded. Using the signals of all autosomal probes, the 95% confidence interval (95% CI) was calculated.…”
Section: Array-cghmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 CNV involves DNA fragments about 1 kb or larger and, despite their heterogeneous distribution throughout the genome, there are no large stretches of the genome exempt from CNV. 5 Nonetheless, fine sequence analyses among the members of a CNV have only been reported for very specific cases known before the CNV concept, such as color vision or immunologic functions. 6,7 Several examples of CNV affecting genes of the immune system have been previously described (for example, a/b-defensins and FcgrIII).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the analysis of 50 orthologous OR genes, suggested that humans also have fewer functional genes and more pseudogenes than chimpanzees, which was later substantiated by a genome-wide comparison of human and chimpanzee OR repertoires ) . More recently, the variation of OR gene number was also identified among different human individuals, which is known as the copy number variation (Trask et al 1998 ;Wong et al 2007) . Interestingly, the level of interspecific divergence relative to that of intraspecific variation in OR gene copy number is not significantly different between functional genes and pseudogenes, suggesting that human intraspecific and human-chimpanzee interspecific OR gene number variations may not have any fitness consequence (Nozawa et al 2007 ;Zhang 2007) .…”
Section: The or Gene Family -The Largest Gene Family In Mammalsmentioning
confidence: 99%